Failure Analysis of Hacksaw Blade - Ibrahim, Muhamad Farhan (IRC, 2016)
Among the equipment in Universiti Teknologi PETRONAS (UTP) fabrication workshop is a 2-horse power hacksaw machine that is used in cutting steel bar and plate. During a cutting work on a steel workpiece, the high-speed tool steel (HSS) hacksaw blade fractured at the contact point between the blade and the workpiece. Therefore, the objective of this project is to analyse the failure, to determine the root cause of the problem and finally suggest solution based on the root cause. Failure investigation technique is used to find the root cause of the failure. Cause and effect analysis had highlighted unfastened workpiece, excessive feed and defects on the blade as the most possible cause of failure. Based on visual inspection, macroscopic and microscopic examination, evidence of fatigue and brittle fracture can be found which closely related to cyclic loading. This support the first hypothesis because excessive vibration can exert cyclic loading on the blade. Therefore, unfastened workpiece is identified as the root cause of the failure. To prevent the failure, excessive vibration must be eliminated by clamping the workpiece to the working table before cutting work.